An Empirical Analysis of Cash Flow and Investment Fluctuations Using Firm-Level Panel Data - Ismail, Abdul Ghafar; Sanusi, Nur Azura (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2005)
Since the pioneering work of Gurley and Shaw (1955), the attempt has been done to justify money as a primary focal point of macroeconomic theorizing. However, other researchers argue that variables such as financial development and indicators are also important to be linked with macroeconomic performance. Here, if money can be thought as means of production and consumer goods as the ultimate end toward which production is directed, and then capital also occupies a position that is both logically and temporarily intermediate between original means and ultimate ends. This temporarily intermediate status of capital is not in serious dispute, but its significance for macroeconomic theorizing is rarely recognized. The firmsâ decision to acquire funds through debt and equity financings affects the capital structure, and, in the firmâs balance sheet, the impact of capital appears to influence the inventory investment. Hence, the significance of capital structure âinduced inventory distortions in the context of firm-level is the basis for our article. The sample for our analysis is compiled from the balance sheets of listed syaria firms in the Kuala Lumpur Stock Exchange for the period 1995-2000.